2005
DOI: 10.1577/m04-024.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Prototype Surface Flow Bypass for Juvenile Salmon and Steelhead at the Powerhouse of Lower Granite Dam, Snake River, Washington, 1996–2000

Abstract: A surface flow bypass takes advantage of the natural surface orientation of most juvenile salmon Oncorhynchus spp. and steelhead O. mykiss by providing a route in the upper water column that downstream migrant fishes can use to pass a hydroelectric dam safely. A prototype structure, called the surface bypass and collector (SBC), was retrofitted on the powerhouse of Lower Granite Dam and was evaluated annually with biotelemetry and hydroacoustic techniques during the 5‐year life span of the structure (1996–2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…Split-beam data were used to estimate the average backscattering cross section of fish for detectability modeling and to determine the direction of fish travel through sampling volumes to allow for meeting the assumptions of the acoustic screen model. The methods used in this study were similar to those used in other hydroacoustic fish passage distribution studies for the USACE (e.g., Johnson et al 2005;Khan et al 2009Ploskey et al 2003Ploskey et al , 2005, including those at Lookout Point Dam on the Middle Fork Willamette River during 2010 ). …”
Section: General Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Split-beam data were used to estimate the average backscattering cross section of fish for detectability modeling and to determine the direction of fish travel through sampling volumes to allow for meeting the assumptions of the acoustic screen model. The methods used in this study were similar to those used in other hydroacoustic fish passage distribution studies for the USACE (e.g., Johnson et al 2005;Khan et al 2009Ploskey et al 2003Ploskey et al , 2005, including those at Lookout Point Dam on the Middle Fork Willamette River during 2010 ). …”
Section: General Approachmentioning
confidence: 99%
“…Johnson et al (2005) describe methods to estimate variances for the passage rate estimates. The variances associated with each passage rate estimate were likely underestimated because between-intake variability in passage within a given turbine unit could not be accounted for because of sampling limitations.…”
Section: Data Processing and Passage Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless, we were able to determine that the BGS did increase B2CC efficiency for fish that navigated to the south gap. However, the overall efficiency of the B2CC only increased for yearling Chinook when comparing 2008 results to those from 2004and 2005(Counihan et. al 2006, suggesting forebay distribution of juvenile steelhead or subyearling Chinook may not have been significantly altered from prior years without a BGS present.…”
Section: Outmigrant Use Of the Bgsmentioning
confidence: 99%
“…The purpose of the BGS was to alter the forebay distribution of smolts migrating downstream by guiding them away from turbines on the south side of the dam and toward a surface bypass collector to the north. Using radio telemetry and hydroacoustics, U.S. Geological Survey (USGS) and PNNL studies showed that about 80% of the fish moving toward the south turbines were successfully diverted north (Johnson et al 2005). Further investigations showed how forebay distribution was affected by the presence of the BGS at Lower Granite.…”
Section: Introductionmentioning
confidence: 99%